Effect Of Special Autonomy Fund And Local Original Revenue To The Percentage Of Poverty In Papua Province In Defense Perspective - Tri Yulianto; Rhevi HS Putri; Nur Khotimah (Return : Study of Management, Economic and Bussines, 2023)
Poverty in Papua Province is an important problem faced by the Indonesian government because it involves issues of national security and defense. This quantitative study aims to obtain information about the Special Autonomy Fund, Regional Original Income and its effect on the percentage level of poverty in Papua Province. This study involves data from the Special Autonomy Fund, PAD and the percentage of poverty in Papua Province from 2004 to 2021. The collected data were analyzed using SPSS multiple linear regression statistics. The results of this study inform that local revenue does not affect the percentage of poverty but the Special Autonomy Fund has an effect on the percentage of poverty in Papua Province. In a defense perspective, the poverty level in Papua Province needs special attention because it involves non-military threats that can lead to the threat of conflict and security. Following up on the findings of this study, the Papua Special Autonomy Fund program is reviewed to continue and it is necessary to prepare a Grand Design for the governance of the Papua Special Autonomy implementation. so that it can be right on target and avoid deviations.